A information technology SISTEM PAKAR PENERAPAN METODE DEMPSTER SHAFER UNTUK MENDIAGNOSA PENYAKIT IKAN KARPER - Fahrozi, Wirhan; Ginting, Erwin; Tahel, Fithry; Ultami, Eliza Yulistya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Carp (Cyprinus carpio) or often known as carp is a freshwater fish that has important economic value and is widespread in Indonesia, Indonesian people are no strangers to this freshwater fish. there are those who keep it as an ornamental fish, but there are also those who consume it as a delicious meal. Therefore it is very possible to cultivate this carp well in order to minimize frequent diseases which result in many deaths, so that it can have an impact on the level of sales and the economy. So it is very possible to build a computerized system based on expert systems in diagnosing carp disease so that it can facilitate access to information for people who need information about carp disease. Website-based system design using the Dempster Shafer Method because it is considered quite flexible and has tolerance for inaccurate data and is based on natural language.